PELAKSANAAN PENDIDIKAN KARAKTER OLEH GURU - Ranti Nazmi; Reindy Rudagi (Bakaba, 2018)
This study focused on the Implementation of Character Education by History Teachers The purpose of the study was to describe describing the implementation of character education and describing the obstacles faced by history teachers in the implementation of character education. The type of research used is qualitative analysis. The results of the study show: 1) The implementation of character education assigns tasks to students, gives direction, to be honest in doing assignments, cooperates together to clean each other, 2) Teacher constraints in carrying out character education there are still students who do not attend congregational prayers and throw trash carelessly, students do not do assignments, cheat when testing, not confidence when told to read the results of the discussion in front of the class, still behave poorly to friends and still argue the results of the discussion by maintaining opinions own. It can be concluded that the implementation of character education by history teachers has been carried out but there are many obstacles in its implementation.